Impact of Flexible Work Arrangements on Employee Engagement among Healthcare Professionals at University of Ilorin Teaching Hospital - Ibrahim, Abdullateef Layi; Olodo, Hameedat Bukola; Aremu, Moriam Adeyemi (NIU Journal of Management Sciences, 2026)
Healthcare professionals in tertiary hospitals operate under heavy workloads, staffing pressures and increasing emotional strain, conditions that can weaken employee engagement and ultimately affect service delivery. This study examined the effect of flexible work arrangements on employee engagement among healthcare professionals at University of Ilorin Teaching Hospital, Kwara State. A descriptive survey design was adopted. Data were collected in 2025 through a structured five-point Likert questionnaire administered to healthcare professionals drawn from a staff population of 3,010, with 307 valid responses used for analysis. Descriptive statistics and multiple regression were employed. The findings show that flexible work arrangements significantly improve employee engagement. In particular, shift rotation, job-sharing arrangements and perceived autonomy in organising daily tasks exerted positive and statistically significant effects, whereas predictable scheduling showed a positive but statistically insignificant effect. The study concludes that flexible work arrangements are an important organisational resource for sustaining vigour, dedication and absorption among healthcare professionals in a resource-constrained hospital setting. It recommends institutionalising fair shift systems, expanding opportunities for task-sharing and strengthening employee autonomy within service requirements. Keywords: Flexible Work Arrangements; Employee Engagement; Healthcare Professionals; Tertiary Hospital; Nigeria.